City lights [videorecording (DVD)] : a comedy romance in pantomime - Chaplin, Charlie, 1889-1977; Cherrill, Virginia, 1908-1996; Lee, Florence, 1888-1962; Robinson, David, 1930- (Chaplin collection (Burbank (Los Angeles County, Calif.)), 2003)
A tramp wins the love of a blind flower girl and attempts to obtain money from a millionaire to help her regain her sight.